STRATEGIC HUMAN RESOURCE MANAGEMENT AND ORGANIZATIONAL PERFORMANCE IN THE DIGITAL ERA - Makhmudova, Gulrukh; Kholmurzayeva, Sarvinoz (International Conference on Business & Management, 2026)
Strategic Human Resource Management (HRM) has become a critical factor in organizational success under conditions of globalization and digital transformation. This article examines the influence of modern HRM practices on organizational performance using international empirical evidence and contemporary management theories. The study applies the IMRAD structure and relies on secondary data obtained from international organizations, scientific journals, and HRM reports. The findings indicate that employee training, digital recruitment, performance management, and employee engagement significantly improve productivity and organizational competitiveness. Furthermore, digital technologies such as Artificial Intelligence (AI) and Human Resource Information Systems (HRIS) enhance decision-making efficiency and workforce management. The study concludes that organizations adopting strategic HRM systems achieve stronger innovation capacity, employee satisfaction, and sustainable development.